Exploiting phage-derived carbohydrate depolymerases for combating infectious diseases - Oliveira, Hugo Alexandre Mendes (2022)
Bacteria are protected against the immune system of their human hosts, as well as against predators such as phages, by expressing diverse surface carbohydrates. Some phages produce specialized depolymerases which can degrade those carbohydrates. Here, we discuss the biological role of depolymerases and how they can be exploited to develop new therapeutic strategies against pathogens.